Modeling of the beef market in Costa Rica: A basic preliminary approach - Solano Pereira, Tatiana (2020)
The beef market in Costa Rica has presented some  changes in consumption at the national level, among other reasons, it is estimated that due to changes in people’s tastes and preferences towards other sources of protein of animal origin. The objective of this investigation was to identify the main variables that determine the supply and demand of bovine meat in Costa Rica, using a structural econometric model and an autoregressive vector model (VAR). The variables that were significant for the forecast of the beef market were the prices of the substitutes and the GDP per capita in terms of demand, while for supply the variables that explain its behavior were the price lagging one period and the price of hydrocarbons. The analysis of the results showed that no applied model managed to fit the supply curve with the explanatory variables. While a forecast of the five-year beef demand curve in the country was achieved, presenting a total movement, due to the fact that a substitution effect has been generated, so that as there are fewer consumers demanding this product, there is a pressure of the market that makes the price decrease. The elasticity of the effect of the price on the demanded quantity of bovine meat indicates an inelastic behavior, which means that the variations in the price do not   significantly affect the demanded quantity.